Anterior segment morphology after acute primary angle closure treatment: a randomised study comparing iridoplasty and medical therapy. Issue 4 (20th August 2015) - Sng, Chelvin C A; Aquino, Maria Cecilia D; Liao, Jiemin; Zheng, Ce; Ang, Marcus; Chew, Paul T K
Abstract : Purpose: To compare the effect of argon laser peripheral iridoplasty (ALPI) and conventional medical therapy in the immediate treatment of acute primary angle closure (APAC) using anterior segment optical coherence tomography (ASOCT). Methods: In this single tertiary centre, prospective comparative study, we randomised 30 consecutive patients with unilateral APAC into two groups: ALPI and medical treatment (n=15 each). Immediately before and 1 h after either intervention, ASOCT imaging was performed. Custom software was used to measure pupil diameter, anterior chamber depth, iris curvature (I-Curv), iris area (I-Area), and the angle opening distance (AOD750), trabecular iris space area (TISA750) and the iris thickness at 750 µm from the scleral spur. The main outcome measure was the change in anterior segment biometrical parameters. Results: The mean age of the patients was 62.8±7.7 years; 13 (43.3%) were male. APAC eyes treated with ALPI had a larger increase in AOD750 (p=0.002) and TISA750 (p=0.006); a smaller increase in I-Area (p=0.004) and a decrease in I-Curv (p=0.001) after treatment compared with those eyes which received medical therapy. An optimal model consisting of age, gender, pretreatment and post-treatment pupil diameter, treatment modality and pretreatment I-Curv explained 53.2% of the variance in AOD750 change after treatment, with the treatment modality accounting for 35.0% and I-Curv accounting for 12.4% of the variability. Conclusions: We observed a greater increase in angle width after ALPI compared with after medical treatment in eyes with APAC. Treatment modality and pretreatment I-Curv were the most significant predictors of angle width change after treatment.